2012
DOI: 10.1177/0734242x12451867
|View full text |Cite
|
Sign up to set email alerts
|

Methane emissions from landfills in Serbia and potential mitigation strategies: a case study

Abstract: Open dumping and landfilling have represented the predominant method of waste management in Serbia during the past decades. This practice resulted in over 3600 waste disposal sites distributed all over the country. The locations of the sites and their characteristics have been determined in the framework of the presented study. The vast majority of disposal sites (up to 3300) are characterized by small deposition depth of waste and total waste volumes of less than 10,000 m(3). Only about 50 landfills in Serbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 19 publications
(18 reference statements)
0
26
0
Order By: Relevance
“…Despite the fact that these sites are smaller than formal urban landills and scatered across peri-urban and rural regions, they are still a signiicant pollution source. Wild dumps must be mapped at municipal level across all regions in order to assess their environmental impact [3,4]. Monitoring of illegal dumping activities is crucial either in high-income countries afecting public lands, roadsides, or water bodies [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that these sites are smaller than formal urban landills and scatered across peri-urban and rural regions, they are still a signiicant pollution source. Wild dumps must be mapped at municipal level across all regions in order to assess their environmental impact [3,4]. Monitoring of illegal dumping activities is crucial either in high-income countries afecting public lands, roadsides, or water bodies [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Disposal sites with an average height above 5 m provide anaerobic conditions in which generation of landfill gas with a high methane content is favored. Most of the existing dumpsites in Serbia can be classified as shallow disposal sites . Abushammala et al .…”
Section: Introductionmentioning
confidence: 95%
“…Most of the existing dumpsites in Serbia can be classified as shallow disposal sites. 12 Abushammala et al showed that, on average, measured CH 4 emissions from sanitary landfills are higher than the emissions measured at the dumpsites. 13 The current situation is characterized by a large number of LFG emission points with low CH 4 content.…”
Section: Introductionmentioning
confidence: 99%
“…; Stanisavljevic et al. ). Brunner and Fellner () estimated that affluent countries spend approximately 0.4% of their gross domestic products (GDPs) on SWM.…”
Section: Introduction and Frameworkmentioning
confidence: 98%
“…infrastructure or a tradition of sustainable SWM practices (Diaz and Otoma 2012;Karagiannidis et al 2009;Sintana et al 2015;Stanisavljevic et al 2012). Brunner and Fellner (2007) estimated that affluent countries spend approximately 0.4% of their gross domestic products (GDPs) on SWM.…”
mentioning
confidence: 99%